Caracterização molecular de digenéticos parasitas de gastrópodes (Mollusca) do baixo rio Ivaí, Paraná, Brasil. - Passere, Mayara Destro (2022)
Thiarids are pantropical gastropods endemic to South America and are found in lentic and lotic freshwater environments. These gastropods act as intermediate hosts for several species of digeneans. However, it is important to consider that there are difficulties for a correct identification of these digeneans in certain stages of the life cycle since the larvae have a reduced size and few morphological characteristics for diagnosis. In this way, techniques based on molecular markers become an extremely important tool, combining the use of ribosomal and mitochondrial regions. Considering that there are no records in the literature of studies involving parasites and gastropods as intermediate hosts in the Ivaí River, this study is the first regarding these relationships. Seventy-six specimens of gastropods were collected. Of these, 21 were parasitized. As for the parasites, 16 different morphotypes were found. The gastropod DNA was amplified using the COI marker. The gastropods showed genetic similarity with Aylacostoma chloroticum with different percentages of identity. As for the parasites, COI and 28S markers were used for DNA amplification. Four different taxa were characterized with both markers. With the mitochondrial marker it was possible to confirm only one genus among the digeneans found. However, the 28S ribosomal marker proved to be more effective for the identification of Ivaí River parasites, showing higher similarity values in relation to sequences available in the databases and lower values of genetic distance. In this way, it was possible to confirm the classification of the morphotypes into two distinct genera.